Chronic neuroleptic-induced mouth movements in the rat: suppression by CCK and selective dopamine D1 and D2 receptor antagonists. - Stoessl, A; Dourish, C; Iversen, S (1989)
Fluphenazine decanoate (25 mg/kg IM every 3 weeks x 6) resulted in spontaneous vacuous chewing mouth movements and jaw tremor in male Sprague-Dawley rats. These movements could be suppressed by the selective D1 or D2 dopamine antagonists SCH 23390 (0.5 mg/kg) and raclopride (0.5 mg/kg), respectively, and by CCK-8S (50 micrograms/kg). Fluphenazine-induced mouth movements were unaffected by the selective CCK antagonist MK-329, and by a dose of physostigmine (50 micrograms/kg) sufficient to stimulate mouth movements in placebo treated rats. Scopolamine (0.1 mg/kg) suppressed spontaneous mouth movements in placebo-treated rats, but the effect on fluphenazine-induced mouth movements was not significant. A higher dose of scopolamine (0.5 mg/kg) did suppress the neuroleptic-induced mouth movements, but also induced hyperactivity, characterized by increased sniffing and grooming. These findings indicate that mouth movements resulting from the chronic administration of neuroleptics to the rat may serve as a useful pharmacological model of tardive dyskinesia in the human, and suggest that a relative increase of D1 activity as well as impaired CCK function may contribute to the pathogenesis of this disorder.